A randomized controlled trial of combination of peppermint, lavender, and turmeric oil for antipruritic agent in pregnant women (Medical Journal of Indonesia, 2021)
BACKGROUND Pruritus is the most common dermatological complaint that occurs during pregnancy, which is around 14–20%. No research related to herbal products to reduce some of the characteristics of pruritus at once has been conducted. This study aimed to assess the effect of blending oil to reduce pruritus based on visual analog scale (VAS). METHODS This was a single-blind, randomized clinical trial that included 57 pregnant women who were at 25–38 weeks of gestation, had a pruritus during pregnancy, a single pregnancy, a level I and II pruritus and a moderate to severe pruritus based on VAS. Pruritus scores were measured using VAS in both the treatment and control groups. The treatment and control groups applied blending oil and placebo, respectively, twice a day after bathing for 2 weeks. Mann–Whitney U, paired t, and chi-square tests were used for the analysis. RESULTS Pruritus reduction in pregnant women who received blending oil was higher than those using placebo (61.08% versus 12.41%, p<0.05). 83% of subjects using blending oils had a reduction of pruritus by >25 mm. Pregnant women who used placebo had a six times greater risk of experiencing pruritus than those who used blending oil (RR = 5.8, 95% CI = 2.613–12.874). CONCLUSIONS Blending oil can be used topically to treat a pruritus in pregnant women.